Poverty reduction and rural finance: From unsustainable programs to sustainable institutions with growing outreach to the poor - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2000)
Only relief achieves short-term poverty reduction, but is ineffective in the long run. Sustainable poverty reduction can only be attained through well-designed long-term development measures. For example, Indonesia is considered one of the most successful countries with regard to poverty reduction. Between 1970 and 1996, it reduced poverty from 60% to 11.5% of its population, a time span of a quarter century during which local financial institutions expanded rapidly. The Asian financial crisis led to a set-back, but also became the departure point for a more sustainable institutional system. (Getubig, Remenyi and Quinones 1997:89; Seibel and Schmidt 1999:8-10) All our experience tells us: there is no short-cut to sustainable poverty reduction and development; and certainly none outside a solid, prudentially regulated institutional framework.
Keywords: 330